2017
DOI: 10.1161/circimaging.116.005461
|View full text |Cite
|
Sign up to set email alerts
|

Sudden Cardiac Death Substrate Imaged by Magnetic Resonance Imaging

Abstract: Sudden cardiac death (SCD) is a devastating event afflicting 350,000 Americans annually, despite the availability of life-saving preventive therapy, the implantable cardioverter defibrillator (ICD). SCD prevention strategies are hampered by overreliance on global left ventricular ejection fraction (LVEF) below 35% as the most important criterion to determine ICD candidacy. Annually in the U.S. alone, this results in approximately 130,000 ICD placements at a cost of over $3 billion but only a 5% incidence per y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(42 citation statements)
references
References 89 publications
0
39
0
3
Order By: Relevance
“…Given immediate capacity for segmented datasets to be fused to live fluoroscopic images, a paradigm of image‐guided personalized therapeutics is emerging. Further, the work described in this sentinel study provides new opportunities to pursue rapid, standardized scar quantification for risk stratification in patients with ischemic cardiomyopathy, a field strongly justified by expanding publications from 2D LGE data …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given immediate capacity for segmented datasets to be fused to live fluoroscopic images, a paradigm of image‐guided personalized therapeutics is emerging. Further, the work described in this sentinel study provides new opportunities to pursue rapid, standardized scar quantification for risk stratification in patients with ischemic cardiomyopathy, a field strongly justified by expanding publications from 2D LGE data …”
Section: Discussionmentioning
confidence: 99%
“…Replacement myocardial fibrosis or “scar” is a recognized substrate for the development of malignant ventricular arrhythmias and is a dominant cause of sudden cardiac death in the population . The most common mechanism of scar formation in the heart is from myocardial infarction (MI), an irreversible death of muscle cells related to blockage of a coronary artery.…”
Section: Introductionmentioning
confidence: 99%
“…39 Prevention of SCD among TOF patients remains a major challenge, especially in reliably identifying the high-risk patients, and perhaps over-reliance on depressed LV function for primary prevention with ICD. 49 The combination of moderate to severe LV systolic dysfunction (EF < 20%) and QRS >180 ms had a strong positive and negative predictive value, 66% and 93%, respectively for predicting SCD. 41 A multicenter observational cohort study of 870 patients identified RV hypertrophy, LV or RV systolic dysfunction (EF <44%) and atrial tachyarrhythmias were predictors of SCD or sustained ventricular tachycardia in young adult patients with repaired TOF.…”
Section: Case 1 Conclusionmentioning
confidence: 90%
“…To accelerate the integration of ML into clinical care, an emphasis on the personalization of these tools for the end user is crucial. Our work is motivated by the well-known clinical challenge of measuring an individual's risk of sudden cardiac death (SCD), a leading cause of death with inherently complex pathophysiology that lends itself to novel approaches [ 17 - 22 ]. Although we focus here on SCD as an illustrative example, the methods we present are applicable more broadly to improving clinical translation of ML, regardless of the specific ML algorithm or clinical application.…”
Section: Introductionmentioning
confidence: 99%